2017
DOI: 10.1016/j.jaerosci.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of consumer monitors to measure particulate matter

Abstract: Recently, inexpensive (<$300) consumer aerosol monitors (CAMs) targeted for use in homes have become available. We evaluated the accuracy, bias, and precision of three CAMs (Foobot from Airoxlab, Speck from Carnegie Mellon University, and AirBeam from HabitatMap) for measuring mass concentrations in occupational settings. In a laboratory study, PM2.5 measured with the CAMs and a medium-cost aerosol photometer (personal DataRAM 1500, Thermo Scientific) were compared to that from reference instruments for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 19 publications
4
77
1
Order By: Relevance
“…The AirBeam and AirVisual both had highly correlated and quantitative results for most of the large cooking and combustion sources, under‐reported the dust and humidifier sources, and missed sources with little mass above 0.3 μm particles. Sousan et al also found the AirBeam under‐reported road dust and welding aerosol. For ambient air measurements in May‐June 2015, the AQ‐SPEC evaluation reported a correlation of 0.66, slopes of 0.10‐0.18, and an offset of 10 μg m −3 to adjust the 3 tested AirBeam monitors to match the regulatory monitor.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The AirBeam and AirVisual both had highly correlated and quantitative results for most of the large cooking and combustion sources, under‐reported the dust and humidifier sources, and missed sources with little mass above 0.3 μm particles. Sousan et al also found the AirBeam under‐reported road dust and welding aerosol. For ambient air measurements in May‐June 2015, the AQ‐SPEC evaluation reported a correlation of 0.66, slopes of 0.10‐0.18, and an offset of 10 μg m −3 to adjust the 3 tested AirBeam monitors to match the regulatory monitor.…”
Section: Resultsmentioning
confidence: 93%
“…The AQ‐SPEC evaluation reported poor correlation ( r 2 < 0.6) between the Foobot and reference monitor for ambient monitoring in July‐September 2016. Sousan et al reported linear correlations with quantitative agreement for salt (slope = 0.5) and road dust (slope = 0.7), but underreporting for welding aerosol (slope = 0.08).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, only a few studies have attempted to compute parameters other than R 2 to gauge the overall performance of low-cost sensor technologies. They typically focus on the RMSE (Holstius et al, 2014;Cross et al, 2017;Zimmerman et al, 2018), the mean absolute error (MAE) and the mean bias error (MBE) (Cross et al, 2017;Zimmerman et al, 2018), and normalized residuals (Sousan et al, 2017;Kelly et al, 2017). In addition to the intercept, slope, and R 2 , we also used ratios of the calibrated PMS3003 PM 2.5 mass concentrations to reference monitor values to examine sensors' post-calibration performance.…”
Section: Sensor Performance Metricsmentioning
confidence: 99%
“…These units could be assembled for a total cost of USD 50 and used in a distributed manner. In controlled laboratory tests, low-cost particle sensors have shown high linearity and stability in comparison with commercial instruments with a known particle size and composition (Wang et al, 2015;Manikonda et al, 2016;Sousan et al, 2016Sousan et al, , 2017Zikova et al, 2017). Several studies in the literature have reported the combination of low-cost particle sensors with "smart" home devices (e.g., temperature, humidity, carbon monoxide sensors, cameras) to provide more comfortable and energy-efficient homes and workplaces (Ivanov et al, 2002;Chung and Oh, 2006;Kim et al, 2010;Bhattacharya et al, 2012;Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%